Crafting Mathematical Minds by Engaging Braille-Tangible 3in1 3D Printed Geoboards Module for Visually Impaired Children - Afiqah Umairah Faizal Azli; Nur Allesya Hana Khairul Anhar; Ts. Dr. Hatika Kaco; Mohd Shaiful Sajab; Fadzidah Mohd Idris; Nurhidaya Mohamad Jan; Siti Munirah Mohd (Semarak ilmu Publishing, 2024)
Non-Indexed Publication